Polymorphisms in the Prothrombin Gene and their Association with Plasma Prothrombin Levels - Ceelie, H.; Bertina, R. M.; van Hylckama Vlieg, A.; Rosendaal, F. R.; Vos, H. L. (Thrombosis and Haemostasis, 2001)
To find genetic causes of high plasma prothrombin levels, an established prothrombotic risk factor, we searched for sequence variations in the prothrombin gene. We selected subjects with the 20210-GG genotype (since the 20210-A allele is already known to be associated with high levels) and elevated prothrombin levels (≥ 130 U/dl) from the Leiden Thrombophilia Study (LETS). No mutations were found in the 1 kb promoter region of the prothrombin gene in seven individuals with an isolated high prothrombin level. Comparison of the allelic frequencies of four different polymorphisms in the prothrombin gene in healthy volunteers and in the control subjects among the selected LETS individuals indicated a higher frequency of the 19911-G allele in the latter group (allele frequency 52 vs. 78%, respectively). Homozygous carriers of the 19911-G allele had 8 U/dl higher plasma prothrombin levels than 19911-AA carriers. This difference in prothrombin levels did not affect the thrombotic risk in 20210-GG carriers. In heterozygous 20210-A carriers the odds ratio increased from 1.6 (95% CI: 0.6-4.3) in subjects with 19911-A to 4.7 (1.6-14.0) in subjects with 19911-G on the other prothrombin allele.
Keywords: Prothrombin; G20210A; A19911G; venous thrombosis